A Brief Apology for a Catholic Moment - Marion, Jean-Luc (University of Chicago Press, 2021)
Intro -- Contents -- Foreword by Kevin Hart -- Address: The Cross without the Banner -- Catholic and French -- Laicity or Separation -- The Utility of Communion -- Envoy: A Catholic Moment -- General Index -- Index of Biblical Passages.